Historical flash floods in England: New regional chronologies and database. (22nd February 2019) - Archer, David; O'Donnell, Greg; Lamb, Rob; Warren, Sarah; Fowler, Hayley J.
Abstract : There is increasing interest in past occurrences of flooding from intense rainfall, commonly referred to as "flash flooding, " and the associated socioeconomic consequences. Historical information can help us to place recent events in context and to understand the effect of low frequency climate variability on changing flash flood frequencies. Previous studies have focussed on fluvial flooding to reconstruct the temporal and spatial patterns of past events. Here, we provide an online flood chronology for the north and south‐west of England for flash floods, including both surface water and fluvial flooding, with coverage from 1700 to 2013 (http://ceg-fepsys.ncl.ac.uk/fc ). The primary source of documentary material is local newspaper reports, which often give detailed descriptions of impacts. This provides a new resource to inform communities and first responders of flood risks, especially those from rapid rise in water level whose severity may be greater than those of accompanying peak flow. Examples are provided of historical flash floods that exemplify how the chronologies can help to place recent floods in the context of the preinstrumental record for: (a) more robust estimates of event return period, (b) identification of catchment or settlement susceptibility to flash flood events, and (c) characterisation of events in ungauged catchments.